Rekreacyjna funkcja lasów miejskich i podmiejskich Warszawy - Gołos, Piotr (Leśne Prace Badawcze, 2013)
To research attitudes to urban and suburban forests, a questionnaire was given to the random sample of 500 Warsaw residents. The most important factors identified by respondents included unlimited accessibility of urban forests as well as their proximity to urban areas. The main forest recreational activities expected by Warsaw residents were longer walks, natural silence and calm, also the absence of litter. A few respondents were receptive to the idea of managed forests as well as natural forests, if improving the quality of recreation is no taken into account. Respondents were willing to be taxed at 52 PLN/person/year in order to receive the desired level of non-timber forest functions in urban forests. Like residents of other regions of Poland, the respondents specified that the protection of air quality and protection of the natural environment are the most important non-timber forest functions. Among the most frequently visited forests located within the borders of Warsaw city are forests close to Choszczówka, Bielański forest and the forest in Koło, which receive respectively 251, 204 and 162 visitors/ha/day. The management of recreational resources in urban forests is expected to be diverse and adapted to the preferences of visitors.